Audit Manajemen Atas Fungsi Keuangan pada CV. Cemara Marina Servisindo di Samarinda - William Budiman; Imam Nazarudin Latif; Nurfitriani Nurfitriani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to assess the factors that cause declining financial performance, the existence of multiple positions in the preparation and examination of financial reports. A management audit of the financial function is also carried out so that the company can assess the effectiveness of financial performance management, especially at CV. Cemara Marina Servisindo as a company engaged in retail trade in general equipment is to discuss the assessment in order to take actions to improve financial management in the company. In this study the theory is audit management, scope and objectives of management audit, types of management audit, characteristics of management audit, and basic principles of management audit. The analytical tool used in this study uses a comparative method, namely comparing the existing systems and procedures in the company with theory and conducting follow-up audits to evaluate audit findings and using audit work papers. The data collection techniques are library research and field research. Based on the results of the analysis previously described, it is known that the internal control system over the financial function at CV. Cemara Marina Servisindo runs less in accordance with the criteria, this is evidenced by the list of findings obtained by the researcher and also through the results of the Financial Management Organization Audit Program research recapitulation table which gets a relative value of 48% which is categorized as “Less Effective”.